Surgical Evaluation of Autologous Platelet-rich Fibrin Membrane as a Coverage Layer in Repair of Urethrocutaneous Fistula after Hypospadias Surgeries: A Randomized Controlled Trial - Ahmed Mohamed Kadry Wishahy; Khaled Salah Ahmed Abdullateef; Sherif Nabhan Kaddah; Alaa Ali Mohamed; Mahmoud Tarek Mohamed (Wolters Kluwer Medknow Publications, 2024)
Purpose: It has recently been reported that the use of platelet-rich fibrin (PRF) as an extralayer over the urethroplasty has been related to a considerable reduction in fistula rates. Due to the lack of evidence supporting the usage of PRF in urethrocutaneous fistula (UCF) repair, we conducted this study to evaluate the efficacy of PRF in patients with UCF. MATERIALS AND METHODS: We conducted a randomized controlled study on patients with distal fistula after hypospadias repair. Patients were randomized into two groups, one with local dartos coverage and the other with PRF coverage layer. Results: In the present study, we included 37 patients; 20 patients underwent local dartos coverage, and 17 patients underwent PRF. The mean age was 22.45 ± 4545 ± 4515 ± ±15.35 (range 11-56) months for the study group and 20.6 ± 66 ± 614 ± ±14.5 (range 6-45) months for the control group. The incidence of recurrent UCF was 11.8% in the treatment group (two patients), whereas the incidence was 30% (six patients) in the control group (P = 0.246). Conclusion: UCF surgery may benefit from the use of PRF as a supportive tissue that promotes wound healing, angiogenesis, and tissue restoration. We believe that the use of PRF as a new approach for UCF repair should be investigated further through clinical studies.